Exposure dependent increases in IL-1beta, Substance P, CTGF and tendinosis in flexor digitorum tendons with upper extremity repetitive strain injury - Fedorczyk, Jane M (2010)
Upper extremity tendinopathies are associated with performance of forceful repetitive tasks. We used our rat model of repetitive strain injury to study changes induced in forelimb flexor digitorum tendons. Rats were trained to perform a high repetition high force (HRHF) handle-pulling task (12 reaches/min at 60 ± 5 % maximum pulling force (MPF)), or a low repetition negligible force (LRNF) reaching and food retrieval task (3 reaches/min at 5 ± 5% MPF), for 2 hrs/day in 30 min sessions, 3 days/wk for 3–12 weeks. Forelimb grip strength was tested. Flexor digitorum tendons were examined at mid tendon at the level of the carpal tunnel for interleukin (IL)-1β; neutrophil and macrophage influx; Substance P, connective tissue growth factor (CTGF) and periostin like factor (PLF) immunoexpression; and histopathological changes. In HRHF rats, grip strength progressively decreased, while IL-1β levels progressively increased in the flexor digitorum peritendon (para- and epitendon combined) and endotendon with task performance. Macrophage invasion was evident in week 6 and 12 HRHF peritendon but not endotendon. Also in HRHF rats, Substance P immunoexpression increased in week 12 peritendon as did CTGF- and PLF-immunopositive fibroblasts, the increased fibroblasts contributing greatly to peritendon thickening. Endotendon collagen disorganization was evident in week 12 HRHF tendons. LRNF tendons did not differ from controls, even at 12 weeks. Thus, we observed exposure dependent changes in flexor digitorum tendons within the carpal tunnel, including increased inflammation, nociceptor-related neuropeptide immunoexpression, and fibrotic histopathology, changes associated with grip strength declines.